THE MAMMALIAN CIRCADIAN CLOCK: GENE REGULATORY NETWORK AND THEIR COMPUTER ANALYSIS - O. A. Podkolodnaya; N. N. Podkolodnaya; N. L. Podkolodnyy (Вавиловский журнал генетики и селекции)
This paper presents the results of the reconstruction and analysis of gene regulatory network of the circadian clock in mammals. Application of graph theory methods makes it possible to analyze the structure of the gene network and identify the central component of circadian clock regulation, which includes the basic regulatory circuits passing through the key element of the circadian clock, the Clock/Bmal1 protein. Cluster analysis has revealed subsystems with clear biological interpretation, which are involved in the functioning of the circadian clock by interacting with the central component. This structural model, which includes the central component and functional subsystems that interact with the central component, can provide grounds for the construction of a mathematical model of the dynamics of the gene network regulating the circadian rhythm.